Deep Brain Stimulation for Dystonia and Device Programming - Ozturk, S.; Kocabicak, E. (Nova Science Publishers, Inc., 2022)
Deep brain stimulation (DBS) is an effective surgical treatment for medication-refractory movement disorders and has been approved by the United States Food and Drug Administration for the treatment of dystonia. The success of DBS in the treatment of dystonia depends on our understanding of the anatomy and physiology of this disorder and close collaboration between neurosurgeons, neurologists, clinical neurophysiologists, neuro-radiologists and neuropsychologists. Pallidal DBS is an established treatment option for medically refractive dystonia. DBS provides relief of the main symptoms of dystonia. It is plausible that the clinical benefits of DBS are due to the disruption of the pathological activity in the cortical-basal-ganglia-thalamic-cortical motor loop. Compared with traditional ablative surgery, DBS has many advantages including fewer side effects and complications, reversibility and programmability of the stimulation, comprehensive improvement of symptoms and long-term steady therapeutic effectiveness. © 2022 by Nova Science Publishers, Inc.